Reform in the House of Commons : the select committee system - Jogerst, Michael A., 1959- (Comparative legislative studies., 1993)
One of the most significant changes in the British House of Commons has been the development in 1979 of a system of select committees charged with monitoring government ministries. Unlike previous experiments in parliamentary reform, these committees are staffed exclusively with backbench MPs, who regularly review executive policies and offer recommendations. Michael Jogerst reappraises the relationship between the executive and legislative branches in light of these new circumstances, which are likely to affect the entire governmental structure of the United Kingdom.